A model-based approach for a practical dosing strategy for the short, intensive treatment regimen for paediatric tuberculous meningitis - Wasmann, Roeland E.; Masini, Tiziana; Viney, Kerri; Verkuijl, Sabine; Brands, Annemieke; Hesseling, Anneke C.; McIlleron, Helen; Denti, Paolo; Dooley, Kelly E. (Frontiers in Pharmacology, 2023)
Following infection with Mycobacterium tuberculosis, young children are at high risk of developing severe forms of tuberculosis (TB) disease, including TB meningitis (TBM), which is associated with significant morbidity and mortality. In 2022, the World Health Organization (WHO) conditionally recommended that a 6-month treatment regimen composed of higher doses of isoniazid (H) and rifampicin (R), with pyrazinamide (Z) and ethionamide (Eto) (6HRZEto), be used as an alternative to the standard 12-month regimen (2HRZ-Ethambutol/10HR) in children and adolescents with bacteriologically confirmed or clinically diagnosed TBM. This regimen has been used in South Africa since 1985, in a complex dosing scheme across weight bands using fixed-dose combinations (FDC) available locally at the time. This paper describes the methodology used to develop a new dosing strategy to facilitate implementation of the short TBM regimen based on newer globally available drug formulations. Several dosing options were simulated in a virtual representative population of children using population PK modelling. The exposure target was in line with the TBM regimen implemented in South Africa. The results were presented to a WHO convened expert meeting. Given the difficulty to achieve simple dosing using the globally available RH 75/50 mg FDC, the panel expressed the preference to target a slightly higher rifampicin exposure while keeping isoniazid exposures in line with those used in South Africa. This work informed the WHO operational handbook on the management of TB in children and adolescents, in which dosing strategies for children with TBM using the short TBM treatment regimen are provided.